1993
DOI: 10.1254/jjp.61.51
|View full text |Cite
|
Sign up to set email alerts
|

Further Studies on the Endogenous Serotonin-Uptake-Inhibitor-Like Substances in the Human Cerebrospinal Fluid

Abstract: ABSTRACT-Theproperties of endogenous substances that inhibit 5HT uptake in human cerebrospinal fluid (CSF) were investigated. Human CSF was loaded onto a Sephadex G-25 column, and each fraction was tested for its ability to inhibit [3H]paroxetine binding in monkey brain preparations. We found four different inhibitory peaks with respective molecular weights (M.W.) of > 12400, 2000 and two of < 1350. The third and fourth peaks (F-3, F-4: < 1350 M.W.) of inhibitory activity were determined to consist of some mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
1
0

Year Published

1995
1995
2002
2002

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
1
1
0
Order By: Relevance
“…We found five different effluent fractions that inhibited [3H]-paroxetine binding. This profile was very similar to that which we obtained for human CSF (9). On the basis of it's Ve/Vo ratio, the first fraction may contain a high molecular weight protein ( Fig.…”
supporting
confidence: 85%
See 1 more Smart Citation
“…We found five different effluent fractions that inhibited [3H]-paroxetine binding. This profile was very similar to that which we obtained for human CSF (9). On the basis of it's Ve/Vo ratio, the first fraction may contain a high molecular weight protein ( Fig.…”
supporting
confidence: 85%
“…We previously reported that human CSF contains substances that modulate [3H]-paroxetine binding sites and 5-HT uptake sites and that the molecular weight of one of these substances was about 2000 (9). However, there are no studies on the changes in the amounts of these endogenous substances in depressive animal models.…”
mentioning
confidence: 99%